Manejo de las yemas de banano estimuladas con som bra como deshije alternativo - Beltrán Salinas, María Mercedes (2012)
On the farm Santa Ines de la Universidad de Machala, we studied the effect of stimulation of buds with shadow on a plantation established aimed to achieve the following objectives: To determine the difference in the growth of shady banana buds in compared with the control; Identify what percentage of functional roots for each treatment there. The present study included five treatments, they use pads of 15 cm in height the same as those covered with rotting pseudostem and a control with 15-cm buds discovered. The variables assessed were recorded in each of the treatments applied, these variables were determined as follows; Plant height at 30, 60 and 90 days after capping; thickness of the pseudostem to 90 days after covered; percentage of functional roots at 90 days after capping; height of buds at 90 days after capping. The data obtained and analyzed using the F test and Duncan, yielded high statistical significance for treatments in plant height to 30, 60 and 90 days, as in stem diameter, percentage of roots and length of the bud. The size of the pseudostem had a positive effect in conjunction with the sombre Organization chart buds, on growth of children after desuckering, surpassing the control without spare. The best treatment for children to achieve greater development to ensure a better return, corresponded to the T3 with pseudostem to 80 cm. The highest percentage of active roots was reached on the pads of 15 cm high with decaying speudotallo 80cm.